THU0416 Rapid tophus resolution in chronic refractory gout patients treated with pegloticase. (15th June 2017) - Mandell, B; Yeo, A; Lipsky, P
Abstract : Background: It has been suggested that the velocity of resolution of tophi in persons with chronic tophaceous gout is related to the serum urate levels. 1 However, few subjects with a persistent serum urate less than 4.0 mg/dL were studied. Pegloticase is a recombinant uricase conjugated to polyethylene glycol approved in the US for treatment of patients with chronic refractory gout. It profoundly decreases serum uric acid in responders to <1 mg/dL. The results from the pegloticase clinical trials provided the opportunity to determine the impact of persistent and markedly low levels of serum urate on the velocity of tophus resolution. Objectives: To assess the velocity of tophus resolution in subjects treated with pegloticase for chronic refractory gout. Methods: This analysis used results from two randomized controlled trials (RCTs) of 6 months duration. 2, 3 For tophus measurements, serial standardized digital photographs were analyzed by a blinded reader using computer-assisted quantitative measurement software. Subjects were defined as responders and nonresponders based upon maintenance of a serum urate <6 mg/dL during intensive monitoring periods after 3 and 6 months of treatment. Results: During the 6 months of the RCTs, a total of 952 tophus measurements were analyzed in 87 subjects, including 341 in 30 responders; 361 in 36 nonresponders receiving pegloticase infusions; and 250 in 21 subjects receiving placebo infusions. Mean serum urate levels in these subjects were 10.1, 0.3 and 0.3 mg/dL at baseline, 3 months and 6 months in responders; 10.7, 8.9 and 9.6 mg/dL in nonresponders; and 10.2, 9.8 and 9.7 mg/dL in placebo treated patients, respectively. At baseline, the mean tophus area in responders was 581.6 +/- 742.7 mm 2 (mean ± SD; n=90 tophi); in nonresponders it was 676.5+/-1416.6 mm 2 (n=93 tophi); and in placebo treated subjects it was 672.9+/-1039.5 mm 2 (n=66 tophi). By regression analysis, the velocity of tophus resolution over the 6 months of treatment was 50.1 mm 2 /month in responders; 14.0 mm 2 /month in nonresponders; and 13.9 mm 2 /month in placebo treated patients (responders versus nonresponders or responders vs placebo treated subjects (p=0.001)). In responders, the mean time to total tophus resolution was estimated to be 347 days (11.5 months, with a range of 5.6–36.4 months). During the 6 month treatment period, the area under the curve (AUC) of multiple serum urate measurements in responders was 6, 067.9+/-6, 781.6 mg/dL hr compared with 34, 647.4+/-8, 586.7 and 42, 451.1+/-6, 396.1 mg/dL·hr in nonresponders and placebo treated subjects, respectively (p<0.001). In responders, there was a significant correlation between the velocity of tophus resolution and serum urate AUC (p=0.009). Conclusions: Pegloticase treatment causes a rapid resolution of tophi in responders as predicted from the profound and persistent serum urate lowering associated with this therapy. References: Perez-Ruiz F et al, Arthritis Rheum 2002; 47:356–60. Sundy JS, et al. JAMA. 2011;306:711–720. Becker MA, et al. Ann Rheum Dis. 2013;72:1469–1474. Disclosure of Interest: B. Mandell Grant/research support from: Horizon, Consultant for: Horizon, Ironwood, A. Yeo Consultant for: Horizon Pharma, P. Lipsky Consultant for: AstraZeneca, Celgene, EMD Serono, GSK, Horizon Pharma, Janssen, Medimmune, Pfizer, Roche, Sanofi, UCB